PHANGS–HST: star cluster spectral energy distribution fitting with cigale. Issue 1 (11th January 2021) - Turner, Jordan A; Dale, Daniel A; Lee, Janice C; Boquien, Médéric; Chandar, Rupali; Deger, Sinan; Larson, Kirsten L; Mok, Angus; Thilker, David A; Ubeda, Leonardo; Whitmore, Bradley C; Belfiore, Francesco; et al.
ABSTRACT: The sensitivity and angular resolution of photometric surveys executed by the Hubble Space Telescope ( HST ) enable studies of individual star clusters in galaxies out to a few tens of megaparsecs. The fitting of spectral energy distributions (SEDs) of star clusters is essential for measuring their physical properties and studying their evolution. We report on the use of the publicly available Code Investigating GALaxy Emission (cigale ) SED fitting package to derive ages, stellar masses, and reddenings for star clusters identified in the Physics at High Angular resolution in Nearby GalaxieS– HST (PHANGS– HST ) survey. Using samples of star clusters in the galaxy NGC 3351, we present results of benchmark analyses performed to validate the code and a comparison to SED fitting results from the Legacy Extragalactic Ultraviolet Survey. We consider procedures for the PHANGS– HST SED fitting pipeline, e.g. the choice of single stellar population models, the treatment of nebular emission and dust, and the use of fluxes versus magnitudes for the SED fitting. We report on the properties of clusters in NGC 3351 and find, on average, the clusters residing in the inner star-forming ring of NGC 3351 are young (<10 Myr) and massive (10 5  M⊙ ) while clusters in the stellar bulge are significantly older. Cluster mass function fits yield β values around −2, consistent with prior results with a tendency to be shallower at the youngest ages. Finally, we explore a Bayesian analysis with additional physically motivated priors for the distribution of ages and masses and analyse the resulting cluster distributions.